2013
DOI: 10.1074/jbc.m113.487959
|View full text |Cite
|
Sign up to set email alerts
|

Traumatin- and Dinortraumatin-containing Galactolipids in Arabidopsis

Abstract: Background:The pathway to form green leaf volatiles is important for plant defense against pathogens and herbivores. Results: Galactolipids with truncated oxoacids are formed as counterparts of green leaf volatiles. Conclusion: Galactolipid-hydroperoxides are substrates for hydroperoxide lyase. Significance: The biosynthetic pathway partly proceeds directly with galactolipids, without the involvement of lipases, to form free fatty acids.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(18 citation statements)
references
References 53 publications
0
18
0
Order By: Relevance
“…Likewise, little is known about the abundance of substrates for HPL. While it was assumed that HPLs use free hydroperoxy fatty acids, more recent results showed that certain HPLs use lipid-bound hydroperoxy fatty acids [47]. Furthermore, does the substrate need to be biosynthesized first, which requires an active lipoxygenase withing the damaged tissue, or are substrates readily available upon damage?…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, little is known about the abundance of substrates for HPL. While it was assumed that HPLs use free hydroperoxy fatty acids, more recent results showed that certain HPLs use lipid-bound hydroperoxy fatty acids [47]. Furthermore, does the substrate need to be biosynthesized first, which requires an active lipoxygenase withing the damaged tissue, or are substrates readily available upon damage?…”
Section: Discussionmentioning
confidence: 99%
“…Nakashima et al [20] identified 12-oxo-9-hydroxy-10E-dodecenoic acid as a glyceride component of galactolipid. Noordermeer et al [1] reported that 12-oxo-9Z-dodecenoic acid was autoxidized to both 12-oxo-9-hydroxy-10E-dodecenoic acid and 12-oxo-11-hydroxy-9Z-dodecenoic acid.…”
Section: Discussionmentioning
confidence: 99%
“…Apart from the case of JAs, where a free carboxylic acid moiety in their biosynthetic intermediate, 12-oxo phytodienoic acid (OPDA), is essential for β-oxidation in peroxisomes, GLV can be formed either as free fatty acids or esterified fatty acids ( Figure 2). When Arabidopsis leaves were disrupted, formation of 12-carbon (C12) oxo acids [12-oxo-(Z)-9-dodecenoic acid (traumatin), and its derivatives], which are counterparts of the HPL reaction, was observed in their free forms, albeit at levels that were substantially lower than those expected from the amounts of GLVs formed (Nakashima et al 2013). Formation of traumatin and its derivatives in mechanically wounded Nicotiana attenuata leaves was also reported (Kallenbach et al 2011).…”
Section: A Lipase-dependent Pathwaymentioning
confidence: 99%
“…galactopyranosyl-glycerol (MGDG-9-OH-traumatin/7-OH-dinortraumatin) through nuclear magnetic resonance and high-resolution MS analyses (Nakashima et al 2013). LC-MS/MS analysis suggested that several other compounds structurally related to MGDG-9-OH-traumatin/7-OH-dinortraumatin were also formed during disruption of Arabidopsis.…”
Section: A Lipase-independent Pathwaymentioning
confidence: 99%
See 1 more Smart Citation